Choosing between environmental conservation and survival: Exploring the link between livelihoods and the natural environment in rural Zimbabwe. Issue 3 (6th July 2021) - Macheka, Mavis Thokozile; Maharaj, Pranitha; Nzima, Divane
ABSTRACT: Poor rural communities in Zimbabwe are increasingly becoming more reliant on the natural environment for their livelihoods. This is in direct response to the prolonged economic crisis facing the country. However, it is unclear how these livelihood strategies affect the natural environment. The purpose of this article is to identify the livelihood strategies used by people living in a rural district in Zimbabwe and investigate how this impacts the natural environment. Drawing on qualitative, semi-structured interviews with a number of key informants, the study found that poor people have resorted to a range of environmentally hazardous strategies as a means of securing their livelihoods. Illegal mining of gold and chrome, sand mining, brick moulding and traditional craft making are common among the rural poor. The interviews reveal that in the context of high levels of poverty, the need for survival outweighs concern for the environment. Additionally, there are gaps in environmental regulation and protection for sustainable livelihoods.